PENERAPAN PSAK NO.105 ATAS SISTEM PEMBIAYAAN SYARIAH MUDHARABAH (STUDI KASUS PADA KSPPS BMT AHSAN BAROKAH MADANI CILACAP) - Wignyo Mudiharso; Tri Nurindahyanti Yulian; Kinasih Rahma Dea (JURNAL EKONOMI, 2022)
This study aims to determine whether the application of transaction accounting in mudharabah financing applied by KSPPS BMT Ahsan Barokah Madani Cilacap is in accordance with PSAK No. 105. This research was conducted in KSPPS BMT Ahsan Barokah Madani Cilacap. The techniques of collecting the date carried by interviews, observations, documentation and literature by review using qualitative descriptive analysis methode it is to describe the application of PSAK No.105 on the mudharabah sharia financing system in KSPPS BMT Ahsan Barokah Madani. The results of this study indicate that: The application of PSAK No.105 On the Mudharabah Financing System in KSPPS BMT Ahsan Barokah Madani, especially in the accounting implementation of the mudharabah sharia financing system, it is in accordance with PSAK No.105. Keywords: Application of PSAK 105, Sharia Financing, Mudharabah Financing